Adult Children Living With Aging Parents: The Association Between Income and Parental Affect. (April 2019) - Gerber, Andrew; Heid, Allison R.; Pruchno, Rachel
This study examined the moderating effect of parental income on the association between parent–child coresidence and parental affect. Secondary analysis was conducted with data from the ORANJ BOWL panel, a representative sample of adults in New Jersey, aged 50 to 74 years ( N = 5, 688). Results indicated that income had a significant moderating effect on the association between the adult child's residential status and parents' positive and negative affect. Among parents with coresident adult children, an observed decline in positive affect and rise in negative affect were amplified as parental income level increased, suggesting differential strains on parental well-being across income levels.